Investigating the roles of translation elongation factor 1B in mammalian cells - Cao, Yuan (The University of Edinburgh, 2012)
Eukaryotic protein translation elongation is tightly controlled by several regulation factors. Eukaryotic translation elongation factor 1B (eEF1B) is the GTP exchange factor for eukaryotic translation elongation factor 1A (eEF1A), which is a G-protein transporting aminoacyl-tRNA to the A site of the ribosome in a GTP dependent manner. The structure of the heavy complex composed of eEF1B and eEF1A (eEF1H) has been widely studied and several models have been proposed, but it is yet not clear how the subunits of the two proteins interact with each other. eEF1B is made up of three subunits, eEF1Bα, eEF1Bδ and eEF1Bγ, and each subunit has been found to be over expressed in different types of cancer. A copy number variant near the eEF1Bδ gene is associated with amyotrophic lateral sclerosis. The two isoforms of eEF1A, eEF1A1 and eEF1A2, are 92% identical, but only eEF1A1 was found to interact with eEF1B subunits in yeast two hybrid (Y2H) experiments. The aims of this PhD project are to investigate the potential involvement of eEF1B in disease, as well as the relationship between eEF1B and eEF1A2. All three eEF1B subunits were present in almost all the cell types and mouse tissues tested. eEF1Bδ showed different variants, the heaviest of which is tissue specific and expressed only in brain and spinal cord. eEF1Bα and eEF1Bδ showed certain abnormalities in transformed cell lines, although in the breast cancer tissues tested no apparent change in eEF1B expression was found. Knockdown of eEF1B did not significantly affect NSC34 cell viability over short periods. In spinal cord sections from motor neurone disease (MND) patients, half of the cases showed a change of eEF1B protein expression compared to normal spinal cord, with either a higher level in glial cells, or a lower level in motor neurones. eEF1B and eEF1A2 were found to be co-expressed in mouse motor neurones, and proximity ligation assay also detected physical interactions between both eEF1A isoforms and eEF1B subunits in mammalian cells, contrary to the previous Y2H study. Experiments in a mouse model with no eEF1A2 expression also support this finding. In heart and skeletal muscle from wasted mice where eEF1A is absent the expression of eEF1Bα and eEF1Bδ was down regulated at both protein and mRNA level, suggesting that eEF1A2 and eEF1B not only physically interact, but also show an interdependence in expression. Overall the results from cultured cells, mouse and human tissues in this study demonstrate the potential involvement of eEF1B in MND, and its interaction with eEF1A, which contributes to the understanding of the non-canonical functions of eEF1B and the structure of eEF1H.
Keywords: Eukaryotic protein translation elongation; eEF1B